Tough talking cowboy - Ryan, Jennifer, 1973- (Ryan, Jennifer, 1973- Wild Rose Ranch series., 2020)
Ex-Army Ranger Drake McGrath has come home to Montana, locked in a battle with himself, lashing out at those who love him most<U+2014>driving away his ex-fiancée and alienating his family. But Adria Holloway sees beyond Drake<U+2019>s tough talk to the raw pain beneath. Raised with her twin sister Juliana by a neglectful mother at the Wild Rose Ranch, Adria also struggles to put the trauma from her past behind her. To help them both, she makes Drake a shocking deal<U+2014>a no-strings relationship that<U+2019>ll help them both face down their demons. Maybe it<U+2019>s a way for her and Drake to heal each other, one sizzling night at a time<U+2026> The heat between them is instant and incredible. But the biggest challenges are yet to come. With Juliana battling her addiction and Drake working on his issues, Adria realizes she can<U+2019>t save everyone. But Drake and Adria discover love can survive tragedy and loss<U+2014>and they can have the life they never thought possible if they just hold on.